La flor de la vida - Abend, Claudia; Abend, Claudia; Loeff, Adriana; Abend, Claudia; Loeff, Adriana; Abend, Claudia; Loeff, Adriana; Bourdette, Jackie; Berrutti, Fabio; Marquez, Daniel; Serkhochian, Fernando (Uruguay : The Film Sales Company, 2017)
A film about love by the people who know it best: the elderly. What begins as a collection of interviews soon focuses on the turbulent love lives of 83-year-old Aldo and his wife Gabriella. After five decades of marriage, Aldo and Gabriella are facing a crisis. Their story, narrated with humor, distance and skepticism, tender and ironic all at once, compels us to face the inevitable question: is love everlasting? This is a love story, or rather, a story about the end of love. Those people who were passionate about each other in the 1950s, who swore to love each other until death, are no longer the same. Their personalities, their interests and their ways of seeing and understanding the world have changed. Has the time come to part ways?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films